Neomycin: sources of contact and sensitization evaluation in 1162 patients treated at a tertiary service - Maria Antonieta Rios Scherrer; Érica Possa Abreu; Vanessa Barreto Rocha (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background: Neomycin is used in several over-the-counter pharmaceutical formulations in Brazil. In Europe and Canada, where it is not freely available, its sensitization frequency is lower than in the United States, where this does not occur. Objective: To present the frequency of sensitization to neomycin observed in a tertiary hospital and the pharmaceutical formulations sold in Brazil containing neomycin. Method: Retrospective analysis of positive results to neomycin, obtained through patch tests performed in a tertiary hospital, from 2009 to 2018 and investigation of topical drugs and vaccines containing neomycin in Brazilian databases available on the internet. Results: Among 1,162 patients, 71 (6%) had positive reactions to neomycin, 65% female and 35% male individuals, 46% were over 50 years old, and 24% had a personal history of atopy. The dermatitis lasted from four months to 20 years. Lesions were located in 69% of the patients on the upper limbs, in 55% they were on the lower limbs, and in 42% they were disseminated in more than 4 sites. Polysensitization was detected in 55% of cases. Of these, 28% were linked to sensitization to rubber allergens and 27% to potassium bichromate. A total of 158 topical presentations of neomycin were found: 79 ointments, 58 creams, 10 ophthalmic solutions, seven otological solutions, one oral solution, two nasal solutions, and one antiseptic powder, in addition to 11 types of vaccines. Study limitations: Retrospective study. Conclusion: Sensitization to neomycin occurred in 6% of the studied population, affecting more females aged over 50 years, with skin lesions located mainly on the upper and lower limbs, in the context of chronic contact dermatitis. Neomycin was found in 135 formulations, most of them available over the counter, as well as in 11 miscellaneous vaccines.